2018
DOI: 10.3390/w10111496
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Water Yield: Assessing the Role of Site and Region-Specific Attributes in Determining Model Performance of the InVEST Seasonal Water Yield Model

Abstract: Simple hydrological models, such as the Seasonal Water Yield Model developed by the Natural Capital Project (InVEST SWYM), are attractive as data requirements are relatively easy to satisfy. However, simple models may produce unrealistic results when the underlying hydrological processes are inadequately described. We used the variation in performance of the InVEST SWYM across watersheds to identify correlates of poorly modeled outcomes of InVEST SWYM. We grouped 749 watersheds from across North America into f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(35 citation statements)
references
References 32 publications
0
33
0
2
Order By: Relevance
“…The current research mainly combines the water balance method with remote sensing and hydrological models to study the difference in AFWC and its spatial distribution in the basin [24,25]. However, most of the existing studies use the average annual runoff to calibrate the model parameters and obtain the average multiyear value of AFWC, which not reflects the AFWC at smaller time scales [26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…The current research mainly combines the water balance method with remote sensing and hydrological models to study the difference in AFWC and its spatial distribution in the basin [24,25]. However, most of the existing studies use the average annual runoff to calibrate the model parameters and obtain the average multiyear value of AFWC, which not reflects the AFWC at smaller time scales [26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, in China InVEST modeling has been used in the design of China's national ecosystem assessment (CEA) tool to address, at both a national and regional scale, changes in ecosystem services [12]. Scordo et al grouped 749 watersheds from across North America into five bioclimatic regions using nine environmental variables to compare the predicted flow patterns to actual flow conditions using the InVEST model [13]. In the UK, Redhead et al [14] validated a hydrological ecosystem service model using widely available global and national-scale datasets; their results suggested that relatively simple models, such as InVEST, can yield accurate ecosystem service measurements.…”
Section: Introductionmentioning
confidence: 99%
“…The Integrated Valuation of Ecosystem Services and Tradeoffs (InVEST) model is a tool used for ecosystem service assessment to support environmental decision making developed in 2007 by the Stanford University, the World Wide Fund for Nature, and the Nature Conservancy (Tallis et al, 2014). The data required by the model are simple and easy to collect (Scordo et al, 2018). Compared with other hydrological models, the water yield model in InVEST has mapping and spatial analysis functions under ArcGIS.…”
Section: Introductionmentioning
confidence: 99%